Event sponsorship and fundraising : an advanced guide / Tom Lunt; Eva Nicotra - Lunt, Tom
Securing sponsorship and other sources of funding for events is becoming increasingly competitive, making differentiation and delivery vital. Event Sponsorship and Fundraising explores this complex area of event management, drawing on both experiential marketing and consumer behaviour theories, and developing critical insights on the dynamics of successful event sponsorship. Its coverage includes professional guidance on prospecting for sponsors, brand activation and evaluation, as well as advice on relationship management, proposal writing and pitching to potential sponsors.